Changes during a growing season in aboveground net primary production of a Minnesota goat prairie - Peterson, Jonathan Glenn (My University, 1983)
Goat prairies are large, steep prairies with shallow soil which exist on south-facing bluffs of the upper Mississippi River. A goat prairie with no signs of disturbance located in extreme southeastern Minnesota was sampled seven times during the 1982 growing season.
Keywords: Prairie plants, Minnesota